2023
DOI: 10.3390/cells12131689
|View full text |Cite
|
Sign up to set email alerts
|

Polarized RPE Secretome Preserves Photoreceptors in Retinal Dystrophic RCS Rats

Abstract: Retinal degenerative diseases, including age-related macular degeneration (AMD) and retinitis pigmentosa, lack effective therapies. Conventional monotherapeutic approaches fail to target the multiple affected pathways in retinal degeneration. However, the retinal pigment epithelium (RPE) secretes several neurotrophic factors addressing diverse cellular pathways, potentially preserving photoreceptors. This study explored human embryonic stem cell-derived, polarized RPE soluble factors (PRPE-SF) as a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…Meanwhile, in our previous investigation, we demonstrated that the concentrated CCM of hESC-RPE, presumed to contain a moderately EV-enriched secretome fraction along with non-EV bound identified growth factors, comprises various neurotrophic growth factors secreted from RPE cells. 13 It is important to distinguish between near pure sEV fraction and a moderately EV-enriched fraction, which may contain other molecules such as growth factors, freely bound in CCM. Such a distinction is critical for identifying predominant bioactive molecules, responsible for observed effects and optimizing the formulation for improved efficacy and safety in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, in our previous investigation, we demonstrated that the concentrated CCM of hESC-RPE, presumed to contain a moderately EV-enriched secretome fraction along with non-EV bound identified growth factors, comprises various neurotrophic growth factors secreted from RPE cells. 13 It is important to distinguish between near pure sEV fraction and a moderately EV-enriched fraction, which may contain other molecules such as growth factors, freely bound in CCM. Such a distinction is critical for identifying predominant bioactive molecules, responsible for observed effects and optimizing the formulation for improved efficacy and safety in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Both scotopic testing involved flash stimuli with intensities ranging from 0.1-25 candela (cd) and photopic testing with with intensities from 0.01-25 cd using the HMsERG Rodent System from OcuScience, NV were conducted as previously described. 13 The raw data from ERG assessments were collected and analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reaching confluence, for each age group, representative fields of view were acquired by bright field and phase contrast microscopy using an Olympus CK40 inverted microscope and Infinity Capture software. Upon reaching confluence, pigmentation in hESC-RPE cells was categorized as follows: grade 0 – pigmentation in 0-10% of the total area, grade 1 – pigmentation in 11-25% of the total area, grade 2 – pigmentation in 26-50% of the total area, grade 3 – pigmentation in 50-80% of the total area, and grade 4 – pigmentation in >80% of the total area (Bennis et al, 2007; Ahluwalia et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…These fully differentiated and polarized RPE cells have demonstrated proven intraocular safety profiles and functional integration in ongoing human clinical trials involving cell transplantation (Schwartz et al, 2015; Mehat et al, 2018; Mandai et al, 2017; Kashani et al, 2018; Kashani et al, 2021). Our group recently reported that concentrated cell culture conditioned media (CCM) of hESC-derived fully differentiated and polarized RPE promoted retinal progenitor cell survival, reduced oxidative stress in APRE-19 cells, and preserved PR and their function in the Royal College of Surgeons (RCS) rat model (Ahluwalia et al, 2023). Accumulating evidence suggests that cell secreted small extracellular vesicles (sEV) play a crucial role in facilitating cell-to-cell communication.…”
Section: Introductionmentioning
confidence: 99%